Nurse-patient communication barriers as perceived by patients in a Teaching hospital, Bharatpur. - Dhungana,Gita (2018)
ABSTRACT: Communication is regarded as an essential component in nursing process. Nurse-patient communication is one of the important factors in providing and effective and quality nursing care and services. The main objective of study was to find out nurse-patient communication barriers as perceived by patients in a teaching hospital. The study has followed the quantitative descriptive cross sectional design and has used the semi-structure interview schedule along with likert rating scale ranging from five to one. At first researcher has prepared list of general wards. Complete enumeration technique was used. Total patients (201) admitted in general wards at least three days of hospital stay were selected. The study has utilized the data analysis tools such as Epi data, SPSS version 21 to analyze the information by using descriptive and inferential statistics. The research was focused on four factors. They are common factors, nurse related factors, patients related factors, and environment related factors. During research, about 78.01% of patients told that most barriers during nurse-patient communication. Among them, patient's related factors were perceived as most barriers. The re was statistical association between common factors with age(p=0.004),marital status (p=0.025), education status (P=0.049), and types of family (p=0.022). Likewise, association also evident between nurse-related factors, types of family (p=0.02). and occupation (p=0.01). Similarly, regarding the environment-related factors, age 9P=0.041), education status (p=0.05) and religion (p=0.009) had statistical association. With regard to perception of overall barriers related to nurse-patient communication, there were no statistical associations with demographic variables. The correlation analysis has found that there was positive correlation in all factors. Among them, nurse-related factors and patient-related factors (r=0.54) have shown moderately positive correlation. It is concluded that majority of patients had perceived level of barriers in overall as most barriers. |Finally, the study has recommended that in-service education, effective supervision and reinforcement scheme, development and utilization of guidelines for nurse-patient communication are the most crucial interventions strategies to improve the nurse-patient communication. Key Words: Effective communication, Barriers, Nurse-patient